Insights about the process and impact of implementing nursing guidelines on delivery of care in hospitals and community settings - Ploeg Jenny; Edwards Nancy; Davies Barbara; Virani Tazim (BMC, 2008)
Abstract Background Little is known about the impact of implementing nursing-oriented best practice guidelines on the delivery of patient care in either hospital or community settings. Methods A naturalistic study with a prospective, before and after design documented the implementation of six newly developed nursing best practice guidelines (asthma, breastfeeding, delirium-dementia-depression (DDD), foot complications in diabetes, smoking cessation and venous leg ulcers). Eleven health care organisations were selected for a one-year project. At each site, clinical resource nurses (CRNs) worked with managers and a multidisciplinary steering committee to conduct an environmental scan and develop an action plan of activities (i.e. education sessions, policy review). Process and patient outcomes were assessed by chart audit (n = 681 pre-implementation, 592 post-implementation). Outcomes were also assessed for four of six topics by in-hospital/home interviews (n = 261 pre-implementation, 232 post-implementation) and follow-up telephone interviews (n = 152 pre, 121 post). Interviews were conducted with 83/95 (87%) CRN's, nurses and administrators to describe recommendations selected, strategies used and participants' perceived facilitators and barriers to guideline implementation. Results While statistically significant improvements in 5% to 83% of indicators were observed in each organization, more than 80% of indicators for breastfeeding, DDD and smoking cessation did not change. Statistically significant improvements were found in > 50% of indicators for asthma (52%), diabetes foot care (83%) and venous leg ulcers (60%). Organizations with > 50% improvements reported two unique implementation strategies which included hands-on skill practice sessions for nurses and the development of new patient education materials. Key facilitators for all organizations included education sessions as well as support from champions and managers while key barriers were lack of time, workload pressure and staff resistance. Conclusion Implementation of nursing best practice guidelines can result in improved practice and patient outcomes across diverse settings yet many indicators remained unchanged. Mobilization of the nursing workforce to actively implement guidelines and to monitor the delivery of their care is important so that patients may learn about and receive recommended healthcare.